Internal processes within the African Easterly Wave system. (16th September 2014) - Poan, D. Emmanuel; Lafore, Jean‐Philippe; Roehrig, Romain; Couvreux, Fleur
<x xml:space="preserve">Abstract</x> The internal processes within an African Easterly Wave (AEW) system, involving mass, dynamic and water vapour fields are investigated using ERA‐I reanalysis, in order to highlight the interactions between convection and AEWs. The budgets of heat, moisture and momentum are analysed during the different phases of AEWs detected using synoptic‐scale precipitable water anomalies as proposed by Poan et al. (2013). The strong climatological meridional gradient of moisture present in the Sahel impacts the shape of the apparent heat source and humidity sink. AEW events over the Sahel are associated with a meridional shift of the intertropical convergence zone (ITCZ). Large exchanges of momentum by small‐scale convective transport are also highlighted between the low‐ and mid‐levels, contributing to the reinforcement of the AEW circulation at 600 hPa and the damping of the monsoon flow. This also appears as a possible mechanism for the vertical tilt of the meridional wind associated with AEWs. Heat budget computation, in the southern flank of the West African Heat‐Low (HL) region where such AEWs occur, reveals that the heating anomalies are mainly driven by the horizontal advections. The vertical circulation acts as a precursor, which initiates the heat transport in the lower troposphere. However, weaker, turbulent mixing also participates in the development of these anomalies, especially in the boundary layer. These budgets ultimately allow the distinct contributions of diabatic and adiabatic processes to be determined.